High levels of interleukin-6 are associated with final infarct size and adverse clinical events in patients with STEMI. Issue 2 (21st December 2021) - Tøllefsen, Ingvild Maria; Shetelig, Christian; Seljeflot, Ingebjørg; Eritsland, Jan; Hoffmann, Pavel; Andersen, Geir Øystein
Abstract : Objective: Inflammation has emerged as a new treatment target in patients with coronary artery disease and inflammation seems to play an important role in ischaemia/reperfusion injury that follows ST-elevation myocardial infarction (STEMI). We aimed to explore the role of acute and sustained interleukin 6 (IL-6) signalling, including soluble IL-6 receptor (IL-6R), with regard to infarct size, adverse remodelling and future cardiovascular events in patients with STEMI. Methods: We included 269 patients with first-time STEMI, symptom duration <6 hours and treated with percutaneous coronary intervention. Blood sampling and cardiac MRI were performed in the acute phase and after 4 months. Clinical events and all-cause mortality were registered during 12-month and 70-month follow-up, respectively. Results: IL-6 levels above median at all sampling points were significantly associated with increased infarct size and reduced left ventricular ejection fraction (LVEF). IL-6 levels in the highest quartile were at all sampling points associated with an increased risk of having an adverse clinical event during the first 12 months and with long-term all-cause mortality. IL-6R was not associated with infarct size, LVEF, myocardial salvage or long-term all-cause mortality. Conclusion: Acute and sustained elevation of IL-6 measured 4 months after STEMI were associated with larger infarct size, reduced LVEF and adverse clinical events including all-cause mortality. The results add important information to the sustained role of inflammation in patients with STEMI and IL-6 as a potential target for long-term intervention. Trial registration number: NCT00922675 .